In Vivo and In Vitro Investigation of the Antibacterial, Cytotoxic, and Immunological Effects of Aqueous Extract from Ziziphus spina-christi Leaves - Abed , Saif Mazeel; Al-Nuaimy , Wafaa Ayad; Albyati , Sheereehan A.M. (Technium BioChemMed, 2024)
Background: The adoption of Ziziphus species medicines for the treatment of inflammatory illnesses is extensive and increasing, nevertheless, the impact of the Ziziphus genus on inflammatory illnesses has not been well studied. Aim of study:- study the Antibacterial, Cytotoxicity of Ziziphus spina-christi leaves extract of in vitro and Immunological effect in vivo , Methods and material : Enterobacter cloacae was obtained from patients from patient with Orthodontics , The Ziziphus spina-christi leaves were obtained from Iraqi market then dried for extraction and 100, 150, 200 mg/ml concentrations were prepared, the experimental design included two parts , in vitro and in vivo, In virto study which estimation the antibacterial activity by agar diffusion methods and Cytotoxicity using WRL-68 cell line with neutral red uptake method, in vivo study was included four groups Group I (Control): daily intraperitoneal injections of normal saline, Group II: injected Intraperitoneal with 100 µl of 1.5 x 108 CFU / ml of E. cloacae, Group III administrated orally with 200 mg/ml of extract , Group IV injected Intraperitoneal with 100 µl of 1.5x108 CFU/ ml of E.cloacae then for 14 day administrated orally with 200 mg/ml with extract then notice the clinical signs of each group evaluation the innate immunity (neutrophil activity) by Nitro-blue tetrazollum (NBT) method , Toll Like receptors-2(TLR-2) and Adaptive immunity (Arthus reaction Delayed hypersensitivity,IL-4,IL-17,IL-10). The results: The results showed that the extract revealed a good antibacterial activity against the studied isolates (E. cloacae ) which that highest activity recorded in 200 mg/ml concentration , The cytotoxicity findings reported the IC50 value of Ziziphus Rugosa extract, which indicates the concentration at which 50% proliferation inhibition of WRL-68 cells occurs, was found to be 280 mg/ml. At the greatest concentration of the extract (200 mg/ml), the cell viability was measured to be 80.08%. On the other hand, the lowest dosage tested (6.25 mg/ml) had no effect on the cells. Furthermore, the mice group that received E.cloacae presented clinical symptoms of illness with clear weight loss and diarrhea, reduction in movement activity through the cage space for 7 days while the mice groups that followed by extract administration presented clinical symptoms of illness for 3 days. On the other side the innate immunity findings that represented with the neutrophilsindex were showed the group that had a combination injection by E.cloacae and extract recorded high values(47.15 %) with valuable difference at (p ≤ 0.05 ) comparison with other studied groups and findings of TLR-2 reported the mice that received only E.cloacae showed highest value (98.12±0.087) with a valuable difference at (p≤ 0.05). In additional the adaptive immunity that represented with the Arthus test and DHT were revealed the group that had a combination administration of extract and E.cloacae showed a higher value than the other group, after 48 hr but the value started decreasing after 72 hr but the highest value recorded ( 4.24± 0.00) after 24 hr with valuable difference at p ≤ 0.05 with other groups. On the other side IL-17,IL-4 and IL-10 showed the groups that received extract with E.cloacae given a high value (424.95±0.46, 100±0.00, 72.18±0.12) respectively which higher than other groups with a significant difference at p≤ 0.05. Conclusion: the current study showed Ziziphus spina-christi leaves aqueous extract have positive effect to regulate the immune response by rising the IL-10 and IL-4 that played anti-inflammatory role also increase IL-17 which contributed to mobilization of neutrophil.